How and Why Does the Malvinas Question Persist? (Global Journal of Human-Social Science, 2024)
In 1982 shortly after the war between Argentina and the United Kingdom over the Malvinas Islands had concluded the United Nations General Assembly - by a large majority - requested that both governments resume negotiations in order to find a peaceful solution to the Sovereignty dispute over said Islands that is it returned the status quo to April 1 of that year More than four decades have passed and the conflict is still ongoing While Argentina complains in various areas the United Kingdom ignores the requests of this actor as well as those made by multiple international forums that seek the advent of the parties to negotiate Here we seek to explore those possible causes contributing to the perpetuation of the conflict over time and in turn how this influences the relationship between societies that maintain historical ties
Keywords: conflict; malvinas; disinformation; desmalvinización; remalvinización